Predicting Students' Digital Entrepreneurial Intention: The Mediating Role of Knowledge and Inspiration - Wibowo, Agus; Narmaditya, Bagus Shandy (Fakultas Ekonomi, Universitas Negeri Semarang, 2022)
This study was intended to investigate how the direct effect of digital entrepreneurship education on digital entrepreneurship intentions and reveal the mediating role of knowledge and entrepreneurial inspiration. Our quantitative approach uses survey methods to address the proposed hypotheses. Approximately 340 students in five and seventh grade from Universitas Negeri Jakarta were participated as volunteers in this study. Moreover, the collected data were analyzed by using SEM-PLS with SmartPLS 3.0. The findings remarked that digital entrepreneurship education could promote students’ digital entrepreneurship intentions. This study provided insights related to psychological aspects in the form of entrepreneurial inspiration as one of the predictor variables and mediators for increasing digital entrepreneurship intentions. This research also confirmed that entrepreneurial knowledge took a role as a mediator for digital entrepreneurial intentions. This research is the first step to exploring further the critical role of digital entrepreneurship education as the right strategy to enhance the number of new entrepreneurs.